Evaluation of awareness & utilisation of clinical practise guideline for management of adult Dengue infection among Malaysia doctors - Ariff, M.I.; Yahya, A.; Zaki, R.A.; Sarimin, R.; Mohamed Ghazali, I.M.; Gill, B.S.; Suli, Z.; Mohd. Yusof, M.A.; Ahmad Lutfi, N.; Thye, S.L.; Ismail, F.; Mahmud, M.; et al. (Public Library of Science, 2017)
Clinical Practice Guideline (CPG) provides evidence-based guidance for the management of Dengue Infection in adult patients. A cross sectional study was conducted to evaluate awareness and utilization of CPG among doctors in public or private hospitals and clinics in Malaysia. Doctors practicing only at hospital Medical and Emergency Departments were included, while private specialist clinics were excluded in this study. A multistage proportionate random sampling according to region (Central, Northern, Southern, Eastern, Sabah and Sarawak) was performed to select study participants. The overall response rate was 74% (84% for public hospitals, 82% for private hospitals, 70% for public clinics, and 64% for private clinics). The CPG Awareness and Utilization Feedback Form were used to determine the percentage in the study. The total numbers of respondent were 634 with response rate of 74%. The mean lengths of service of the respondent were 13.98 (11.55).A higher percentages of doctors from public facilities (99%) were aware of the CPG compared to those in private facilities (84%). The percentage of doctors utilising the CPG were also higher (98%) in public facilities compared to private facilities (86%). The percentage of Medical Officer in private facilities that utilizing the CPG were 84% compares to Medical Officer in public facilities 98%. The high percentage of doctors using the CPG in both public (97%) and private (94%) hospitals were also observed. However, only 69% of doctors in private clinics utilised the CPG compared to doctors in public clinics (98%). Doctors in both public and private facilities were aware of the dengue CPG. However, most doctors in private clinic were less likely to utilise the CPG. Therefore, there is a need to increase the level of CPG utilisation especially in private clinics.